Insights on the role of cytokines in carious lesions - Gonçalves, Lucélia Lemes [UNESP]; Kim, Eui; Bortolatto, Janaína Freitas; Buzalaf, Marilia Rabello; Alreshaid, Lulwah; Prakki, Anuradha (Editora Cubo, 2023)
Objectives: The dentin-pulp immune response to caries pathogenesis is still poorly understood due to the complex interplay of the involving processes. The aim of this review was to explore the role of cytokines and its relevance in the pathogenesis of dental caries. Results: Dental caries can result in a host inflammatory response in the dental pulp, characterized by the accumulation of inflammatory cells leading to the release of inflammatory cytokines such as Interleukin-4 (IL-4), Interleukin (IL-6), Interleukin-8 (IL-8) and Tumor necrosis factor–α (TNF-α). IL-4 seems to be correlated to the depth of carious lesions; IL-6 is strongly correlated to caries disease and is considered a potent biomarker; IL-8 can be a potent biomarker for both caries and other changes present in the pulp and, its release is correlated to TNF-α and IL-6; TNF-α plays an important role not only in caries progression, but also in other pathological processes. Conclusion: Specific mediators have a great potential to serve as biomarkers alluding to the presence and progress of caries disease, urging further investigations in the field.
Insights sobre o papel das citocinas em lesões cariosas
Keywords: Biomarkers; Cytokines; Dental caries; Dental pulp; Interleukins